Assessment of liquid, semi-solid, and powder formulations for delivering Trichoderma sp. as maize seed coating against Peronosclerospora maydis - Arsyadmunir, Ahmad; Pawana, Gita; Triwidyantari, Rina Aulia; Khoiri, Syaiful (Universitas Trunojoyo Madura, 2024)
Downy mildew, caused by Peronosclerospora sp., is a major disease impacting maize (Zea mays L.) production, resulting in significant yield losses. This study evaluated the effectiveness of three Trichoderma sp.-based seed coating formulations (liquid, semi-solid, and powder) in reducing disease incidence and severity in maize. The experiment followed a completely randomized design with four treatments, including a control, replicated five times. The parameters assessed included disease incidence, severity, and control effectiveness over 35 days after inoculation. Results showed significant differences among treatments. The powder formulation (T3) demonstrated superior performance, reducing disease incidence by 42.3% and severity by 44.99% compared to the control (T0), which exhibited the highest disease levels. Control effectiveness of the T3 formulation reached 53.81%, categorized as moderately effective. The enhanced efficacy of the powder formulation is attributed to its ability to maintain high Trichoderma sp. populations, enabling sustained antagonistic activity through parasitism, antibiosis, and induced systemic resistance. These findings underline the potential of Trichoderma sp.-based seed coatings, particularly in powder form, as an environmentally friendly and practical alternative for managing downy mildew in maize.